FORMATION OF A SANATORIUM-RESORT COMPLEX COMPLEX REGION CAUCASIAN MINERAL WATERS IN THE 1920 YEARS OF THE TWENTIETH CENTURY - Julia Fedorovna Zolnikova (Наука. Инновации. Технологии, 2022)
The region of Caucasian Mineral Waters is one of the oldest and leading Russian recreation areas, on which territory there are a variety of recreational resources: hydromin-eral, mud, etc. This contributed to the formation of Caucasian Mineral Waters region as the largest sanatorium complex of the country. The article discusses about one of the significant historical stages of development of the resort region of Caucasian Mineral Waters - 1920 of the 20-th century. The peculiarities of the development of sanatorium-resort complex of the region during the study years were identify in connection with events in the country and government regulations. It is shown how to expand the network of sanatoriums and material and technical base, improved resort infrastructure, developing recreational activities and occurred the formation of new Spa treatment, and also presents information about dynamics of holidaymakers during the period.